1994
DOI: 10.1038/nsb1294-891
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the N-terminal SH3 domain of GRB2 complexed with a peptide from the guanine nucleotide releasing factor Sos

Abstract: Src-homology 3 (SH3) domains mediate signal transduction by binding to proline-rich motifs in target proteins. We have determined the high-resolution NMR structure of the complex between the amino-terminal SH3 domain of GRB2 and a ten amino acid peptide derived from the guanine nucleotide releasing factor Sos. The NMR data show that the peptide adopts the conformation of a left-handed polyproline type II helix and interacts with three major sites on the SH3 domain. The orientation of the bound peptide is oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
99
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 38 publications
7
99
1
Order By: Relevance
“…Our data contradict recent reports suggesting that GRB2-SH3N mediates binding to THEMIS (5,21). Although the reason for this discrepancy is unclear, our data do agree with published reports indicating that GRB2-SH3N preferentially binds to motifs conforming to the consensus PxxPxR (15), such as the type II polyproline helix in SOS (24), and displays only negligible affinities toward RxxK motifs (12,15). This leaves open the possibility that GRB2, via SH3N, helps in bridging LAT and THEMIS to an unknown partner.…”
Section: Discussioncontrasting
confidence: 57%
“…Our data contradict recent reports suggesting that GRB2-SH3N mediates binding to THEMIS (5,21). Although the reason for this discrepancy is unclear, our data do agree with published reports indicating that GRB2-SH3N preferentially binds to motifs conforming to the consensus PxxPxR (15), such as the type II polyproline helix in SOS (24), and displays only negligible affinities toward RxxK motifs (12,15). This leaves open the possibility that GRB2, via SH3N, helps in bridging LAT and THEMIS to an unknown partner.…”
Section: Discussioncontrasting
confidence: 57%
“…We have observed that the presence of a second arginine at the C-terminal end of the proline-rich peptide (PVPPPVPPRR) increases the affinity for Grb2 and gives a two times higher tryptophan fluorescence signal, suggesting that the arginines come close to the conserved tryptophan of the SH3 domain [4]. However, the NMR structure of the isolated Grb2 N-SH3 shows that the second arginine does not bind to the SH3 [34,35], it seems to help this region of the peptide to adopt a helical conformation that places the first arginine in an appropriate position (Fig. 3).…”
Section: Properties Of Grb2 Sh3 Domainsmentioning
confidence: 92%
“…The acidic cluster around positions 30, 31, 33 of the N-ter SH3 is the most mobile loop of the structure. Surprisingly, it was found that the SH3 domains of Grb2 bind proline rich peptides in the opposite orientation than Abl, PI3Kinase and Fyn [34][35][36]. This is made possible by the pseudo-symetry of the polyproline II helix.…”
Section: Properties Of Grb2 Sh3 Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, molecules whose shapes complement the protein interaction clefts of the ligand surfaces are likely to block receptor binding (4). Previously, several linear peptides with extended polyproline type II (PP II ) 1 conformation have been shown to block ligand-acceptor complexes involved in molecular recognition (5)(6)(7). Acceptors are typically large proteins with measurable affinity for specific ligands; the latter can be presented as a small peptide sequence within an exposed loop on the surface of a large protein.…”
mentioning
confidence: 99%